Pos BUMDES dan Smart Assets Business Sebagai Peningkatan Kinerja BUMDES - Supriyati; Bahri, Ramadhan Syaeful (SULUH: Jurnal Abdimas, 2022)
This Community Service has the aim of developing a Smart Asset Business application for BUMDes governance to make it easier for BUMDes employees and increase the competence of BUMDes employees in managing assets, transactions and making financial reports, then preparing BUMDes so that they can become legal entities. With various programs to achieve goals such as the development of smart asset business applications, training for BUMDes employees in the TokoDesa unit, assistance for licensing BUMDes legal entities and other activities that support the achievement of the goals of this service, it is known that 100% of respondents consider that this service has a positive impact on improving quality. HR and the quality of BUMDes itself. With the development of a smart asset business website, they consider that they can provide clear and complete information to the people of Pagerwangi Village in particular and the Indonesian people in general. They also consider this website to be used as a promotional page and an introduction to BUMDes and BUMDes products. In the asset management section, and BUMDes transactions, it is a crucial part and they find it very helpful to make standard-compliant financial reports in an easy way.